Bibliometric Analysis on Cyber-Attacks in Naval Sensors and Systems - de Albuquerque, Carlos Eduardo Pires; Machado, Raphael Carlos Santos; de Sa, Alan Oliveira; de Toledo, Carlos Rafael Barros (2022 IEEE International Workshop on Metrology for the Sea; Learning to Measure Sea Health Parameters (MetroSea), 2022)
Cyber-attacks in the maritime-port sector have demonstrated their ability to impact the world economy, generating losses. This threat is heightened by the relevance of maritime activities in global economy. The maritime sector is changing the processes by the digital transformation. The cyber threats and associated losses are likely to grow. The scenarios of attacks on ports and ships come out of hacktivism and are effectively characterized as criminal activity. The damage threatens lives and the environment, as well as impacting the global supply chain. This work looks for identifier the current stage of academic research on cyberattacks in naval sensors and systems through a bibliometric analysis. The knowledge about the present researches projects and the key persons will contribute to find the best way to developing protect solutions. The results demonstrate that is a very recent theme, which is constantly evolving due to the accelerated world digital transformation and subject generates added value for society. Researches can be provided solutions to mitigate to impact in the economy, supply chains security, sustainability and safety of Life at sea.